Ultrastructural characterisation of the olfactory mucosa of the armadillo Dasypus hybridus (Dasypodidae, Xenarthra) - Ferrari, Carina Cintia (2000)
The ultrastructure of the olfactory mucosa of the armadillo Dasypus hybridus was studied. A comparison with the olfactory mucosa of another armadillo (Chaetophractus villosus) was made. The olfactory mucosa of D. hybridus shows many features which are similar to those of other mammals. Interestingly, it differs from the olfactory mucosa of the armadillo C. villosus. A suggestion is made that these differences may be due to differences in the digging habits of these species. In Dasypus, the supporting cells (SCs) showed dense vacuoles, multivesicular bodies and lysosome-like bodies probably related with the endocytotic system. The SCs show a dense network of SER presumably associated with xenobiotic mechanisms. The olfactory receptor neurons exhibit lysosome-like bodies and multivesicular bodies in their perikarya. These organelles suggest the presence of an endocytotic system. Duct cells of Bowman's glands exhibit secretory activities. Bowman's glands are compound-branched tubulo-acinar mixed glands with merocrine secretory mechanisms.